Study on the Adsorption Effect of Renewable Biochar Based on Energy Gain. (31st October 2021) - Yang, Zhanghang; Xu, Qixiang; Zhang, Ruiqin; Huang, Qianming; Liu, Mingxin
Abstract : This paper provides sufficient evidence on how the crop-residual-derived charcoal could effectively restore the soil polluted by the heavy metal. In this paper, straw char at three temperatures of 300°C, 500°C, and 700°C, labeled as RS300, RS500, and RS700, was prepared by low temperature pyrolysis technique using straw as raw material, and the competitive adsorption desorption of Pb 2+, Cd 2+, Cu 2+, and Zn 2+ in acidic solution and the mechanism were investigated by static adsorption experiments. Since the crop-residual-derived charcoal could effectively restore the nutritional structure of the soil, which contributes to preventing the decrease in grain yield, and it is also a kind of renewable environment-friendly resource by itself, which could be used in control the pollution of heavy metal ions, it is expected that the crop-residual-derived charcoal will be a new adsorption material that could be used to control the heavy metal pollution in the future; the adsorption effect of biochar as new adsorption material on heavy metal ions has a distinct advantage over traditional adsorbent materials, and biochar is a renewable energy source, which is cheap and better for recycling resources.